2022
DOI: 10.1021/acsomega.1c06590
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Structural Behavior of Orthorhombic Mn3(VO4)2: Raman Spectroscopic and X-ray Diffraction Investigations

Abstract: The effect of high pressure on the structure of orthorhombic Mn3(VO4)2 is investigated using in situ Raman spectroscopy and X-ray powder diffraction up to high pressures of 26.2 and 23.4 GPa, respectively. The study demonstrates a pressure-induced structural phase transition starting at 10 GPa, with the coexistence of phases in the range of 10–20 GPa. The sluggish first-order phase transition is complete by 20 GPa. Importantly, the new phase could be recovered at ambient conditions. Raman spectra of the recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…19 According to the results summarized above, the HP behavior of Ca 3 V 2 O 8 is different from that of other orthovanadates with equivalent chemical formulae. For instance, Zn 3 V 2 O 8 , Ni 3 V 2 O 8 , and Ba 3 V 2 O 8 remain stable up to at least 15, 20 23 21 and 29 GPa 22 respectively. Mn 3 V 2 O 8 and Sr 3 V 2 O 8 exhibit pressureinduced phase transitions around 10 GPa 23 and 13.8 GPa 22,24 respectively, and Cu 3 V 2 O 8 chemically decomposes at 1.35 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 According to the results summarized above, the HP behavior of Ca 3 V 2 O 8 is different from that of other orthovanadates with equivalent chemical formulae. For instance, Zn 3 V 2 O 8 , Ni 3 V 2 O 8 , and Ba 3 V 2 O 8 remain stable up to at least 15, 20 23 21 and 29 GPa 22 respectively. Mn 3 V 2 O 8 and Sr 3 V 2 O 8 exhibit pressureinduced phase transitions around 10 GPa 23 and 13.8 GPa 22,24 respectively, and Cu 3 V 2 O 8 chemically decomposes at 1.35 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zn 3 V 2 O 8 , Ni 3 V 2 O 8 , and Ba 3 V 2 O 8 remain stable up to at least 15, 20 23 21 and 29 GPa 22 respectively. Mn 3 V 2 O 8 and Sr 3 V 2 O 8 exhibit pressure-induced phase transitions around 10 GPa 23 and 13.8 GPa 22,24 respectively, and Cu 3 V 2 O 8 chemically decomposes at 1.35 GPa. 25 Such different results from various HP studies in the M 3 V 2 O 8 family, and the apparent contradictions between different HT studies, clearly show that further investigation into the pressure and temperature evolution of the Ca 3 V 2 O 8 is needed to understand its structural behavior under extreme conditions of pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the high pressure (HP) community has also put the focus on this family of compounds, which have demonstrated a variety of remarkable physical behaviors under pressure. X-ray diffraction (XRD) and Raman methods were used to study Mn 3 V 2 O 8 in its orthorhombic low-temperature structure; an irreversible phase transition at 10 GPa was discovered, but the new phase has not been identified yet . In contrast, it has been demonstrated that Zn, Ni, and Mg orthovanadates are stable up to 15, 23, and 25.7 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…From the fundamental point of view, the high-pressure (HP) behavior of M 3 V 2 O 8 vanadates has also been the focus of recent studies [14][15][16]. X-ray diffraction experiments have shown that Zn 3 V 2 O 8 [14] and Ni 3 V 2 O 8 [15] remain stable in the low-pressure phase up to 15 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction experiments have shown that Zn 3 V 2 O 8 [14] and Ni 3 V 2 O 8 [15] remain stable in the low-pressure phase up to 15 GPa. In Mn 3 V 2 O 8 [16], the onset of a structural phase transition has been located beyond 10 GPa. On the other hand, the bulk moduli of M 3 V 2 O 8 vanadates have been determined to cover a range of values from 100 GPa to 140 GPa.…”
Section: Introductionmentioning
confidence: 99%